Liquid crystal polymer film and method for producing the same

A liquid crystal polymer film with controlled linear expansion coefficients and flat fillers addresses the issue of disrupted orientation caused by spherical fillers, reducing CTE and warpage in FCCLs, enhancing mechanical strength and flexibility.

JP7609288B2Active Publication Date: 2025-01-07MURATA MFG CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023545644
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-06-01
Filing Date
2022-08-31
Publication Date
2025-01-07
Estimated Expiration
2042-08-31

AI Technical Summary

Technical Problem

The mixing of spherical fillers with LCP resin disrupts the orientation of the resin, leading to increased CTE and warpage and distortion in flexible copper-clad laminates (FCCLs).

Method used

A liquid crystal polymer film containing flat fillers with an average aspect ratio of 3 or more and an average inclination of 15° or less with respect to the main surface direction, along with controlled linear expansion coefficients, is used to produce a flexible copper-clad laminate.

Benefits of technology

The solution effectively reduces the CTE within the main plane of the LCP film, minimizing warpage and distortion in FCCLs, while maintaining mechanical strength and flexibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609288000005
    Figure 0007609288000005
  • Figure 0007609288000006
    Figure 0007609288000006
  • Figure 0007609288000007
    Figure 0007609288000007
Patent Text Reader

Abstract

A liquid crystal polymer film including a liquid crystal polymer and a filler, the filler including a flat filler, the average aspect ratio of the filler being 3 or more, and the average inclination of the filler relative to the main surface direction of the liquid crystal polymer film being within 15°.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a liquid crystal polymer film and a method for producing a liquid crystal polymer film. [Background technology]

[0002] Liquid crystal polymers (LCPs) have smaller dielectric constants and dielectric loss than polyimide resins, which are conventional circuit board materials, and also have an extremely small water absorption rate, meaning that fluctuations in dielectric properties due to water absorption are minimal. Therefore, they are used in high-frequency circuit boards, especially high-frequency FPC boards (flexible circuit boards). However, there is a demand for further improvements in high-frequency properties, and for example, the addition of fillers with excellent electrical properties is being considered.

[0003] Known methods for producing an LCP film from an LCP resin include, for example, a melt extrusion method and a solution casting method. The melt extrusion method is a method for forming an LCP film by extruding molten LCP resin from a slit-shaped die. The solution casting method is a method for forming an LCP film or a flexible copper-clad laminate (FCCL) by applying a varnish made by dissolving an LCP raw material such as an LCP pellet in a solvent to a copper foil and drying it.

[0004] In this manufacturing method, the molecules of the LCP resin are strongly oriented in the direction of the main surface of the film, resulting in an LCP film with a linear expansion coefficient (coefficient of thermal expansion: CTE) equivalent to that of the copper used for wiring. By making the CTE of the copper and LCP film in the direction of the main surface equivalent, it is possible to prevent the accumulation of warping and distortion caused by the dimensional difference between the copper and the LCP resin.

[0005] Here, Patent Document 1 (JP 2014-111699 A) describes a method of mixing a plate-like filler with a liquid crystal polymer powder and producing a filler-mixed liquid crystal polymer film by melt extrusion. Also, Patent Document 2 (JP 2004-315678 A) describes a liquid crystal polymer resin composition containing a liquid crystal polyester and an aprotic solvent, and a method of producing a liquid crystal polymer film made of the resin composition by melt casting, and also describes that a filler may be added. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2014-111699 A [Patent Document 2] JP 2004-315678 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, when spherical or other fillers are mixed into LCP resin, the orientation of the LCP resin becomes disordered, the CTE increases, and warping and accumulation of distortion occur in the FCCL.

[0008] In view of the above problems, the present disclosure aims to provide a liquid crystal polymer film containing a filler, in which the linear expansion coefficient within the main surface of the liquid crystal polymer film is controlled, and a flexible copper-clad laminate having a liquid crystal polymer film with a controlled linear expansion coefficient. [Means for solving the problem]

[0009] The liquid crystal polymer film of the present disclosure is A liquid crystal polymer film comprising a liquid crystal polymer powder and a filler, The filler includes a flat filler, The average aspect ratio of the filler is 3 or more; The average inclination of the filler with respect to the main surface direction of the liquid crystal polymer film is within 15°. Effect of the Invention

[0010] According to the present disclosure, it is possible to provide a liquid crystal polymer film containing a filler and having a controlled linear expansion coefficient within the main surface of the liquid crystal polymer film, and a flexible copper-clad laminate having a liquid crystal polymer film with a controlled linear expansion coefficient. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a photograph of a cross section of the liquid crystal polymer film in Example 1. As shown in FIG. [Diagram 2] FIG. 2 is a photograph of a cross section of the liquid crystal polymer film in Example 2. [Diagram 3] FIG. 3 is a photograph of a cross section of the liquid crystal polymer film in Comparative Example 1. As shown in FIG. [Figure 4] FIG. 4 is a photograph of a cross section of the liquid crystal polymer film in Comparative Example 2. As shown in FIG. [Diagram 5] FIG. 5 is a photograph of the flexible copper-clad laminate in Example 1. [Figure 6] FIG. 6 is a photograph of the flexible copper-clad laminate in Comparative Example 1. [Figure 7] FIG. 7 is a flow diagram showing the manufacturing process of the liquid crystal polymer film of the embodiment. [Figure 8] FIG. 8 is a flow chart showing a first modified example of the manufacturing process of the liquid crystal polymer film according to the embodiment. [Figure 9] FIG. 9 is a flow chart showing a second modified example of the manufacturing process of the liquid crystal polymer film according to the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, embodiments of the present disclosure will be described, but the present disclosure is not limited to these.

[0013] <Liquid crystal polymer film> A liquid crystal polymer film (LCP film) according to one embodiment of the present disclosure comprises a liquid crystal polymer (LCP) and a filler, the filler comprising a flat filler, the average aspect ratio of the filler being 3 or more, and the average inclination of the filler relative to the thickness direction of the LCP film being within 15°.

[0014] (Liquid Crystal Polymer) The liquid crystal polymer is not particularly limited, but examples thereof include thermotropic liquid crystal polymers, etc. Thermotropic liquid crystal polymers are aromatic polyesters synthesized mainly from monomers such as aromatic diols, aromatic dicarboxylic acids, and aromatic hydroxycarboxylic acids, and exhibit liquid crystallinity when melted.

[0015] The molecules of liquid crystal polymers have a negative coefficient of linear expansion (CTE) in the axial direction of the molecular axis and a positive CTE in the radial direction of the molecular axis.

[0016] The liquid crystal polymer is preferably free of amide bonds. Examples of thermotropic liquid crystal polymers free of amide bonds include a copolymer of parahydroxybenzoic acid, terephthalic acid and dihydroxybiphenyl (block copolymer of parahydroxybenzoic acid and ethylene terephthalate) having a high melting point and low CTE, called 1-type liquid crystal polymer, or a copolymer (block copolymer) of parahydroxybenzoic acid and 2,6-hydroxynaphthoic acid having a melting point between 1-type liquid crystal polymer and 2-type liquid crystal polymer, called 1.5-type (or 3-type).

[0017] In differential scanning calorimetry (DSC) of the LCP film, the liquid crystal polymer preferably has a temperature difference (ΔTm=Tm2-Tm1) calculated by subtracting the first melting point (Tm1) from the second melting point (Tm2) between a first melting point (Tm1) of the liquid crystal polymer in the LCP film measured at a first heating rate and a second melting point (Tm2) in the LCP film measured at a second heating rate after the measurement of the first melting point (Tm1), of 10° C. or more. If the temperature difference (ΔTm) is 10° C. or more, the LCP fibers in the LCP film are sufficiently fused together, and furthermore, the LCP molecular chains in the LCP film are further entangled with each other, so that the mechanical strength of the LCP film is further improved.

[0018] The method for measuring the first melting point (Tm1) and the second melting point (Tm2) in this embodiment will be described in detail below.

[0019] First, in differential scanning calorimetry (DSC) of an LCP film, the temperature at an endothermic peak that appears when the LCP film is heated from room temperature to a temperature equal to or higher than the melting point of the liquid crystal polymer at a relatively fast first heating rate (for example, 20°C / min) to melt the film is taken as the first melting point (Tm1). If multiple endothermic peaks are observed, the highest temperature among the temperatures at the multiple endothermic peaks may be taken as the first melting point (Tm1) of the LCP in the LCP film. By heating the LCP film at a relatively fast heating rate as described above, the change in the crystal structure of the liquid crystal polymer in the liquid crystal polymer film is suppressed. Therefore, the first melting point (Tm1) is a melting point that reflects the crystal structure of the liquid crystal polymer in the LCP film, compared to the second melting point (Tm2) measured after the measurement of the first melting point (Tm1).

[0020] After measuring the first melting point (Tm1), the melted LCP film is cooled to a temperature below the recrystallization temperature of the liquid crystal polymer (for example, below 200°C). The cooled LCP film is then heated at a second heating rate (for example, 20°C / min) to a temperature above the melting point of the liquid crystal polymer, and the temperature at the endothermic peak that appears when this is determined as the second melting point (Tm2). If multiple endothermic peaks are observed at this time, the highest temperature among the temperatures at the multiple endothermic peaks may be determined as the second melting point (Tm2) of the LCP in the LCP film.

[0021] (Liquid Crystal Polymer Powder) The LCP film according to an embodiment of the present disclosure can be produced by a production method described below using a liquid crystal polymer powder (LCP powder) made of the above-mentioned liquid crystal polymer. The LCP powder contains fibrous particles (liquid crystal polymer fibers: LCP fibers) made of a liquid crystal polymer.

[0022] The LCP fibers contained in the LCP powder are not particularly limited as long as they contain a fibrous portion, which may be linear or may have branches.

[0023] The average diameter of the LCP fibers is 2 μm or less, preferably 1.4 μm or less, and more preferably 1 μm or less. The average diameter of the LCP fibers is, for example, 0.07 μm or more. The smaller the average diameter of the LCP fibers, the less the LCP fibers will ride over each other during the production of the LCP film. This makes it easier for the LCP to be oriented in-plane during the production of the LCP film, and reduces the coefficient of linear expansion (CTE) in the main plane of the LCP film and the amount of warping of the flexible copper clad laminate (FCCL). The average aspect ratio of the LCP fibers is preferably 10 or more and 500 or less, and more preferably 10 or more and 300 or less.

[0024] The average diameter and average aspect ratio of the LCP fibers are measured by the following method.

[0025] LCP powder made of LCP fibers to be measured is dispersed in ethanol to prepare a slurry in which 0.01% by mass of LCP powder is dispersed. At this time, the slurry is prepared so that the water content in the slurry is 1% by mass or less. Then, 5 to 10 μL of this slurry is dropped onto a slide glass, and the slurry on the slide glass is allowed to dry naturally. By allowing the slurry to dry naturally, the LCP powder is arranged on the slide glass. Next, a predetermined area of ​​the LCP powder placed on the slide glass is observed with a scanning electron microscope (SEM) to collect 100 or more image data of the particles (LCP fibers) constituting the LCP powder. In collecting the image data, the area is set according to the size of each LCP particle so that the number of image data is 100 or more. In addition, in order to prevent the occurrence of missed image data collection or measurement errors for each LCP particle, the magnification of the SEM is appropriately changed to 500x, 3000x, or 10000x to collect the image data. Next, using the collected image data, the longitudinal dimension and width dimension of each of the LCP fibers are measured. For one LCP fiber captured in each of the image data, the direction of the straight line connecting both ends of the longest path from one end of the fiber through approximately the center of the particle to the opposite end of the fiber is defined as the longitudinal direction. The length of the straight line connecting both ends of the longest path is measured as the longitudinal dimension. In addition, the particle size in the direction perpendicular to the longitudinal direction is measured at three different points in the longitudinal direction of each particle of the LCP powder, and the average value of the dimensions measured at these three points is defined as the width direction dimension (fiber diameter) per particle of the LCP powder. Furthermore, the ratio of the longitudinal dimension to the fiber diameter [longitudinal dimension / fiber diameter] is calculated to obtain the aspect ratio of the LCP fiber. The average value of the fiber diameters measured for 100 LCP fibers is taken as the average diameter. The average aspect ratio is determined as the average value of the aspect ratios measured for 100 LCP fibers.

[0026] The fibrous particles may be contained in the LCP powder as aggregates of the fibrous particles.

[0027] In addition, the axial direction of the LCP molecules constituting the fibrous particles tends to coincide with the longitudinal direction of the fibrous particles. This is believed to be because, when an LCP powder is produced, destruction occurs between a plurality of domains formed by bundling the LCP molecules, causing the axial direction of the LCP molecules to be oriented along the longitudinal direction of the fibrous particles.

[0028] In the LCP powder, the content (number ratio) of particles other than fibrous particles (aggregated particles that are not substantially fibrous) is preferably 20% or less. For example, when the LCP powder is placed on a flat surface, particles with a maximum height of 10 μm or less are fibrous particles, and particles with a maximum height of more than 10 μm are aggregate particles.

[0029] The LCP powder preferably has a D50 (average particle size) value of 13 μm or less, as measured by particle size measurement using a particle size distribution measuring device based on a laser diffraction scattering method.

[0030] The LCP powder may further have its surface previously treated with ultraviolet light (UV treatment). By previously treating the surface of the LCP powder, the number of oxygen atoms located on the surface of the LCP powder increases. When the number of oxygen atoms located on the surface of the LCP powder increases, the intermolecular force between the molecules constituting the surface of the LCP powder and the molecules constituting the surface of the filler in the LCP film increases. This improves the interfacial adhesion between the LCP powder and the filler, which in turn improves the strength of the LCP film.

[0031] (Filler) The filler of the present disclosure includes a flat filler, and may include a filler of a shape other than a flat shape. In addition, the "flat filler" in the present disclosure includes a filler obtained by heating and compressing a filler used as a raw material (hereinafter, sometimes referred to as a "filler raw material"), a flat filler raw material, a filler obtained by agglomerating a spherical or other filler raw material to form a flat aggregate, and the like.

[0032] The filler raw material is not particularly limited, and either an organic filler or an inorganic filler can be used. Examples of the organic filler include perfluoroalkoxy fluorine (PFA) resin, polytetrafluoroethylene (PTFE), polyphenylene ether (PPE), polyimide, polyamideimide, polyetherimide, polyethersulfone, cyclic polyolefin, syndiotactic polystyrene, and polyphenylene sulfide. Examples of the inorganic filler include powders of inorganic oxides such as talc, alumina, and silica, carbon powder, ceramic powder, and glass powder.

[0033] The filler raw material provides the LCP film with necessary properties such as dielectric constant, thermal conductivity, etc. The filler raw material is preferably an organic filler from the viewpoint of flexibility of the LCP film. As the organic filler, it is preferable to use PFA resin, PTFE, or PPE. The filler raw material may be used alone or in combination of two or more kinds.

[0034] The shape of the filler raw material is not particularly limited, and irregular fillers, plate-like fillers, granular fillers, etc. can be used.

[0035] The filler raw material has a D50 (average particle size) value of 5 μm or less, preferably 3 μm or less, and more preferably 1 μm or less, as measured by particle size measurement using a particle size distribution measuring device by a laser diffraction scattering method.

[0036] In addition, the average particle size of the filler raw material is preferably smaller than the average diameter of the LCP fiber. When a filler is mixed with the LCP, the orientation of the LCP fiber is disturbed, but by doing so, the disturbance of the orientation of the LCP fiber can be suppressed.

[0037] The filler raw material may be surface-treated by plasma treatment. The plasma treatment is, for example, in-liquid plasma treatment. In the in-liquid plasma treatment, first, the filler raw material is mixed with a 50% by mass ethanol aqueous solution to obtain an ethanol slurry. A gas is bubbled in the ethanol slurry. An electric discharge is performed in the bubbling gas. This electric discharge generates a plasma gas, which can treat the surface of the filler raw material. As a result, the chemical bonds of the molecules on the surface of the filler atoms are cut, and a predetermined functional group is generated according to the type of the filler raw material. When the filler raw material is, for example, a PFA resin, a carboxyl group is generated on the surface. When a carboxyl group is generated on the surface, the intermolecular force due to hydrogen bonds between the molecules constituting the surface of the LCP powder in the LCP film and the molecules constituting the surface of the filler increases. This improves the interfacial adhesion between the LCP powder and the filler. As a result, the strength of the LCP film improves. The gas is, for example, nitrogen.

[0038] The filler in the present disclosure has an average aspect ratio of 3 or more, and includes flat shapes such as thin flakes, flaky scales, and flakes. Here, the average aspect ratio of the filler is the average aspect ratio calculated by measuring the major axis and minor axis of a plurality of fillers by a method described later. The major axis represents the diameter in the longest direction of the filler, and the minor axis represents the longest length in the direction perpendicular to the major axis. The aspect ratio of each filler is the ratio of the major axis to the minor axis. If the average aspect ratio of the filler is less than 3, the LCP molecules are oriented in the thickness direction of the LCP film, so that the CTE in the main surface of the LCP film cannot be reduced. The average aspect ratio of the filler is preferably 4 or more.

[0039] In addition, the average inclination of the filler relative to the principal surface direction of the LCP film is within 15°. If the average inclination of the filler relative to the principal surface direction of the LCP film exceeds 15°, the LCP molecules are oriented in the thickness direction of the LCP film, so that the CTE in the principal surface of the LCP film cannot be reduced. The average inclination of the filler relative to the principal surface direction of the LCP film is preferably within 10°.

[0040] The average aspect ratio of the filler and the average inclination in the thickness direction of the LCP film can be determined by solidifying the periphery of any cross section of the LCP film or FCCL containing the filler to be measured with resin, polishing it, photographing the polished cross section using an SEM, and performing image analysis on the photographed image.

[0041] The filler and LCP powder can be identified by binarizing the SEM image using image processing software ("ImageJ") as image analysis software. Here, binarization refers to a process of converting the darkness of each pixel into two values, 1 and 0, using a certain reference value (threshold value). Specifically, the SEM image is subjected to binarization processing using image processing software ("ImageJ") to obtain a binarized image for recognizing the filler. Here, the binarization processing is performed, for example, based on the brightness of pixels. Although there is no clear value for the brightness threshold value in the binarization processing, it is preferable to adjust the threshold value so that the ratio of light and dark areas matches the actual volume mixture ratio of the filler and LCP powder.

[0042] Based on the binarized image, the major axis, minor axis, and inclination of the multiple fillers in the microscope image with respect to the thickness direction of the LCP film are calculated. Here, the number of fillers to be measured is at least 50 or more, and preferably 100 or more. In addition, it is preferable to perform image analysis in multiple fields of view in the same LCP film or FCCL, but even when performing image analysis in a single field of view, image analysis of 50 or more fillers may be performed as described above, and the average value may be used as the average aspect ratio and the average inclination with respect to the thickness direction of the LCP film. In the present disclosure, the values ​​measured for 50 or more fillers are the average aspect ratio and average inclination. The field of view may be, for example, 50 μm long x 100 μm wide. Note that fillers with an aspect ratio of the major axis to the minor axis within 1.1 are considered to be true spheres, with an aspect ratio of 1 and an inclination of 45°.

[0043] Regarding the average aspect ratio of the filler, first, the area of ​​each filler is measured by the following formula (1). Area (μm 2 ) = radius of major axis (μm) × radius of minor axis (μm) × pi... Equation (1) Next, the average of the areas measured for 50 or more fillers is taken as the average area, and the area average ratio of each filler is calculated by the following formula (2). Area average ratio = area (μm 2 ) ÷ average area (μm 2 )...Equation (2) The larger the cross-sectional area of ​​the filler, the greater the influence it has on the orientation of more LCP fibers and the greater the effect it has on the CTE. Therefore, the corrected aspect ratio of the filler is calculated using the following formula (3). Corrected aspect ratio = measured aspect ratio × area average ratio (3) In the present disclosure, the average of the above corrected aspect ratios is defined as the average aspect ratio.

[0044] In addition, the larger the cross-sectional area of ​​the filler, the greater the influence it has on the orientation of many LCP fibers and the greater the influence it has on the CTE. Therefore, the correction slope of the filler is calculated using the following formula (4). Corrected inclination (°) = Measured inclination (°) × Area average ratio (4) In the present disclosure, the average of the above corrected slopes is defined as the average slope.

[0045] <Method of manufacturing liquid crystal polymer film> Each step of the manufacturing method of this embodiment will be described below.

[0046] As shown in FIG. 7, the method for producing a liquid crystal polymer film according to this embodiment includes a dispersing step (S1), a matting step (S2), a hot pressing step (S3), and a metal foil removing step (S4).

[0047] First, the method for producing the LCP powder used in the dispersion step (S1) will be described in detail. The LCP powder can be produced, for example, by carrying out the following coarse pulverization step, fine pulverization step, coarse particle removal step, and fiberization step in this order.

[0048] The shape of the raw material (LCP raw material) made of LCP used to prepare the LCP powder can be, for example, uniaxially oriented pellets, biaxially oriented film, powdered LCP, etc. The LCP constituting the LCP raw material is the same as the LCP constituting the above-mentioned LCP fiber.

[0049] (Coarse grinding process) In the coarse pulverization step, the LCP raw material is coarsely pulverized. For example, the LCP raw material is coarsely pulverized with a cutter mill. The size of the coarsely pulverized LCP particles is not particularly limited as long as it can be used as a raw material for the fine pulverization step described later. The maximum particle size of the coarsely pulverized LCP particles is, for example, 3 mm or less.

[0050] It is not always necessary to carry out the coarse pulverization step. For example, if the LCP raw material can be used as a raw material for the fine pulverization step, the LCP raw material may be used directly as a raw material for the fine pulverization step.

[0051] (Fine grinding process) In the fine pulverization step, the LCP raw material (after the coarse pulverization step) is pulverized while being dispersed in liquid nitrogen to obtain granular finely pulverized liquid crystal polymer (finely pulverized LCP).

[0052] In the pulverization step, it is preferable to use media to pulverize the LCP raw material dispersed in liquid nitrogen. The media is, for example, beads. In the pulverization step of this embodiment, it is preferable to use a bead mill, which has relatively few technical problems, from the viewpoint of handling liquid nitrogen. An example of a device that can be used in the pulverization step is the liquid nitrogen bead mill "LNM-08" manufactured by IMEX.

[0053] The granular finely pulverized LCP obtained by the fine pulverization process preferably has a D50 of 50 μm or less as measured by a particle size distribution measuring device using a laser diffraction scattering method, which can prevent the granular finely pulverized LCP from clogging the nozzle in the fiberization process described below.

[0054] (Coarse particle removal process) Next, in the coarse particle removal step, coarse particles are removed from the granular pulverized LCP obtained in the pulverization step. For example, the granular pulverized LCP is sieved with a mesh to obtain granular pulverized LCP that falls below the sieve, and the granular LCP that remains above the sieve is removed to remove the coarse particles contained in the granular pulverized LCP. The type of mesh may be appropriately selected, and an example of the mesh is one with an opening of 53 μm. The coarse particle removal step is not necessarily required.

[0055] (Fiberization process) Next, in the fiberization process, the granular LCP is crushed by a wet high-pressure crushing device to obtain LCP powder. In the fiberization process, the finely pulverized LCP is first dispersed in a dispersion medium for the fiberization process. The finely pulverized LCP to be dispersed does not need to have coarse particles removed, but it is preferable that the coarse particles have been removed. Examples of the dispersion medium for the fiberization process include water, ethanol, methanol, isopropyl alcohol, toluene, benzene, xylene, phenol, acetone, methyl ethyl ketone, diethyl ether, dimethyl ether, hexane, or mixtures thereof.

[0056] Then, the finely pulverized LCP dispersed in the dispersion medium for the fiberization process, i.e., the finely pulverized LCP in a paste or slurry state, is passed through a nozzle under high pressure. By passing through the nozzle under high pressure, the shear force or collision energy due to the high-speed flow in the nozzle acts on the LCP, crushing the granular finely pulverized LCP, and the fiberization of the LCP progresses, and an LCP powder consisting of fine LCP fibers can be obtained. The pressure during the pressurization is, for example, 100 MPa or more and 300 MPa or less. From the viewpoint of applying a high shear force or high collision energy, it is preferable that the nozzle diameter of the nozzle is as small as possible within a range in which the finely pulverized LCP does not clog the nozzle. Since the particle diameter of the granular finely pulverized LCP is relatively small, the nozzle diameter of the wet high-pressure crushing device used in the fiberization process can be made small. The nozzle diameter is, for example, 0.2 mm or less.

[0057] As described above, a plurality of fine cracks are formed in the granular pulverized LCP. Therefore, the dispersion medium penetrates into the inside of the pulverized LCP through the fine cracks by pressurization in the wet high-pressure crushing device. Then, when the paste-like or slurry-like pulverized LCP passes through the nozzle and is placed under normal pressure, the dispersion medium that penetrates into the inside of the pulverized LCP expands in a short time. The dispersion medium that penetrates into the inside of the pulverized LCP expands, and destruction proceeds from the inside of the pulverized LCP. Therefore, fiberization proceeds to the inside of the pulverized LCP, and the LCP molecules are separated into domain units in which they are aligned in one direction. Thus, in the fiberization process in this embodiment, by defibrating the granular pulverized LCP obtained in the fine pulverization process in this embodiment, an LCP powder having a lower content of aggregated particles and consisting of fine LCP fibers can be obtained, compared to the LCP powder obtained by crushing the granular LCP obtained by the conventional freeze-pulverization method.

[0058] In the fiberization step in this embodiment, the finely pulverized LCP may be crushed multiple times with a wet high-pressure crushing device to obtain LCP powder, but from the viewpoint of production efficiency, it is preferable to perform crushing with the wet high-pressure crushing device a small number of times, for example, 5 times or less. Also, from the viewpoint of obtaining LCP powder with a smaller average diameter, it is preferable to perform crushing with the wet high-pressure crushing a large number of times, for example, 6 times or more and 90 times or less.

[0059] (UV treatment process) The method for producing an LCP powder according to this embodiment may further include a UV treatment step. In the UV treatment step, the LCP powder obtained in the fiberization step is surface-treated with ultraviolet light. Specifically, the LCP powder obtained in the fiberization step is subjected to a wet UV treatment. The ultraviolet treatment time is, for example, 1 hour or more and 5 hours or less.

[0060] (Dispersion process: S1) In the dispersion step, which is the first step in the method for producing an LCP film, the LCP powder and the filler material are dispersed in a dispersion medium to form a paste or slurry. In this manner, in the present embodiment, since a fine fibrous LCP powder and a filler material with a small average particle size are used, the LCP powder and the filler material can be dispersed in a highly viscous dispersion medium. As a result, a homogeneous LCP film can be produced.

[0061] Examples of the dispersion medium used in the dispersion step include butanediol, water, ethanol, terpineol, a mixture of water and ethanol, etc. For example, when butanediol is used as the dispersion medium, a mixture of the LCP powder and the filler in a paste form is obtained. When a mixture of water and ethanol is used as the dispersion medium, a mixture of the LCP powder and the filler in a slurry form is obtained.

[0062] The mixing ratio of the LCP powder and the filler raw material may be, for example, 5:5 to 8:2 by volume. If the volume ratio of the filler raw material is greater than that of the LCP powder, the filler will be the main component in the mixture, making it difficult to form the mixture into a film. It is more preferable to mix the LCP powder and the filler raw material at a volume ratio of 5:5 to 7:3. In other words, it is more preferable that the ratio of the content of the filler to the total content of the liquid crystal polymer and the filler in the liquid crystal polymer film is 30 vol% or more and 50 vol% or less. By making the content ratio of the filler 30 vol% or more and 50 vol% or less, it becomes easy to achieve both the desired effect of improving electrical properties by the filler and the molding of the LCP film.

[0063] (Matting process: S2) Next, in the matting process, the mixture of the LCP powder and the filler in the form of a paste or slurry is dried to form a liquid crystal polymer fiber mat (LCP fiber mat). In one embodiment of the present invention, the matting process includes, for example, a coating process and a drying process.

[0064] In the coating process, a mixture of the LCP powder paste and the filler is applied to a metal foil such as a copper foil. In the coating process, the mixture of the LCP powder paste and the filler is applied to a metal foil such as a copper foil as described above, but instead of the metal foil, a polyimide film, a PTFE film, or a composite sheet made of a reinforcing material such as a glass fiber fabric and a heat-resistant resin that does not easily adhere to LCP may be used. This makes it easy to industrially produce the LCP film.

[0065] Next, in the drying process, the mixture of the LCP powder paste and the filler applied to the copper foil is heated and dried to evaporate the dispersion medium. By this heating and drying, an LCP fiber mat is formed on the metal foil such as the copper foil.

[0066] In addition, in the drying process, the dispersion medium is gradually removed from the mixture of the LCP powder paste and the filler, so that the total thickness of the mixture of the LCP powder paste and the filler gradually decreases during drying, and therefore the thickness of the LCP fiber mat becomes thinner than the total thickness of the mixture of the LCP powder paste and the filler formed on the copper foil.

[0067] Furthermore, as the total thickness of the mixture of the paste-like LCP powder and the filler gradually decreases during drying, the longitudinal direction of the fibrous particles in the LCP powder changes. Specifically, among the fibrous particles, the fibrous particles having the longitudinal direction in the total thickness direction of the mixture of the paste-like LCP powder and the filler tilt so that the longitudinal direction faces the main in-plane direction of the copper foil. Therefore, the longitudinal direction of the fibrous particles in the formed LCP fiber mat is anisotropic.

[0068] In the matting step, a mixture of LCP powder and filler in a paste form may be applied onto the LCP fiber mat formed on the metal foil by the drying step, and then the mixture may be dried to evaporate the dispersion medium. In this manner, the matting step may include a coating step and a drying step repeated in this order. This allows an LCP fiber mat having a desired basis weight to be obtained. In addition, when the coating step and the drying step are repeatedly performed, a mixture in which the mixing ratio of the LCP powder and the filler is changed for each coating step may be used. This allows an LCP fiber mat capable of forming an LCP film having desired properties to be obtained.

[0069] In the matting step in this embodiment, instead of the coating step and drying step, a mixture of the slurry-like LCP powder and the filler may be formed into an LCP fiber mat by a papermaking method. The papermaking method does not require the use of a special dispersion medium (e.g., expensive terpineol) used in the coating step. In addition, the papermaking method allows the dispersion medium used in the dispersion step to be easily recovered and reused. In this way, the papermaking method allows the LCP film to be produced at low cost.

[0070] Specifically, in the mat-making process using the papermaking method, a slurry of LCP powder and a filler are first papered onto a mesh, a nonwoven microporous sheet, or a woven fabric, and then the mixture of the slurry of LCP powder and the filler arranged on the mesh is heated and dried to obtain an LCP fiber mat.

[0071] (Hot pressing process: S3) Next, in the hot pressing step, the LCP fiber mat is hot pressed to obtain an LCP film. Also, by hot pressing the LCP fiber mat, the filler material or the aggregate of the filler material becomes flat, and the filler is oriented so as to be inclined at 15° or less with respect to the main surface direction of the LCP film. Specifically, in the hot pressing step, the LCP fiber mat is hot pressed together with the copper foil. As a result, the hot pressing step also serves as a step of bonding the LCP film and the copper foil to each other, so that the LCP film with the copper foil bonded thereto can be obtained at low cost. Note that, when heating is performed for a long time in the hot pressing step, it is preferable to hot press the LCP fiber mat in a vacuum.

[0072] Heating in the hot pressing process is performed to bond the LCP fibers together. However, in order to easily flatten the filler raw material or the aggregates of the filler raw material, when the average particle size of the filler raw material exceeds 1 μm, it is preferable to perform hot pressing within a range of ±10° C. of the melting point of the filler raw material. Note that when the average particle size of the filler raw material is 1 μm or less, the orientation of the LCP fibers is not easily disturbed, so there is no restriction on the heating temperature. However, when the LCP fibers are surface-treated with ultraviolet light, and when the filler raw material is plasma-treated, it is preferable that the heating temperature in the hot pressing process is equal to or lower than the melting point of the LCP fibers, from the viewpoint of bonding the LCP fibers and the filler raw material to each other at the interface between them.

[0073] The pressure in the heat press step is preferably 3 MPa or more, more preferably 5 MPa or more, so that the filler raw material becomes flat and the filler is oriented at an inclination of 15° or less with respect to the main surface direction of the LCP film. If the pressure is too high, the LCP resin melts and flows, so the pressure is preferably 10 MPa or less.

[0074] The holding time in the hot pressing step is not particularly limited and may be, for example, 5 seconds or more, or may be 10 seconds or more. In addition, since the filler raw material becomes flatter by holding for a long time, the holding time may be, for example, 3 minutes or more, or may be 5 minutes or more.

[0075] In addition, in the hot pressing process, a composite sheet or the like made of a reinforcing material such as a polyimide film, a PTFE film, or a glass fiber fabric and a heat-resistant resin that does not easily adhere to LCP may be sandwiched between the press used in the hot pressing process and the LCP fiber mat.

[0076] Alternatively, instead of the polyimide film, an additional copper foil may be sandwiched between the press and the LCP fiber mat. In this case, an LCP film with copper foil bonded to both sides can be obtained. The LCP film with copper foil bonded to both sides can be used as a double-sided copper foil FCCL.

[0077] The outer dimensions of the LCP film formed by the hot pressing process in the thickness direction, i.e., the planar dimensions along the film surface, are approximately the same as those of the LCP fiber mat before the hot pressing. Then, by the hot pressing, the fibrous particles of the LCP powder in the LCP fiber mat, which have a longitudinal direction along the thickness direction of the LCP fiber mat, are heated while being pressed down in the main in-plane direction of the copper foil. Since the LCP constituting the LCP powder has a molecular axial direction in the longitudinal direction of the fibrous particles, the axial direction of the LCP molecules is also pressed down in the main in-plane direction of the copper foil. Therefore, except for the molecules constituting the aggregated particles, the axial direction of each of the molecules constituting the LCP is oriented along the main in-plane direction of the LCP film across the thickness direction of the LCP film. Therefore, in the formed LCP film, the main orientation direction of the LCP molecules tends to be along the main in-plane direction of the copper foil, i.e., the main in-plane direction of the LCP film.

[0078] Similarly, the filler is heated while being pressed down in the in-plane direction of the copper foil by the hot press, so that the major axis of the filler is oriented in the in-plane direction of the LCP film across the thickness direction of the LCP film.

[0079] It is believed that these factors contribute to a reduced CTE within the main surface of the LCP film of this embodiment.

[0080] In addition, when copper foil is laminated to the LCP film, it is possible to reduce the CTE of the LCP film to be approximately the same as the CTE of the copper foil (approximately 18 to 20 ppm / °C), which can suppress defects such as warping due to thermal shrinkage in the LCP film laminated with the copper foil.

[0081] (Metal foil removal process: S4) Finally, if necessary, the metal foil bonded to the LCP film may be removed by etching, etc. This results in a single LCP film with no metal foil bonded thereto.

[0082] The method for producing a liquid crystal polymer film according to this embodiment may further include other steps.

[0083] (Heat treatment process: S5) Fig. 8 is a flow diagram showing a first modified example of the manufacturing process of the liquid crystal polymer film of the embodiment. As shown in Fig. 8, the manufacturing method of the liquid crystal polymer film according to the present embodiment may further include a heat treatment step (S5) after the hot pressing step (S3). The heat treatment step (S5) may be performed before the metal foil removing step (S4) as shown in Fig. 8, or may be performed after the metal foil removing step (S4).

[0084] In the heat treatment step (S5), the LCP film obtained in the hot press step or the FCCL obtained in the metal foil removal step is heated in a heating furnace such as a hot air circulating furnace. The heat treatment can be performed by known means such as a hot air circulating furnace, a heated roll, an infrared heater, etc. In the heat treatment step (S5), the LCP is not pressurized as in the hot press step (S3). Therefore, even in a relatively high temperature environment close to the melting point of the LCP, there is little concern that the LCP will flow significantly. As a result, it is possible to suppress the change in thickness of the LCP film and the generation of a brittle layer in the LCP film due to interface shear stress.

[0085] The heating temperature in the heat treatment step (S5) is preferably at least 30°C lower than the melting point of the LCP powder and at most 10°C higher than the melting point of the LCP (when simply referring to the "melting point of the LCP" in this specification, the "melting point of the LCP" means the melting point of the LCP powder, i.e., the melting point of the LCP raw material, and the "melting point of the LCP" is the above-mentioned second melting point (Tm2)). By heat treating the LCP film (in the case of FCCL, the resin layer made of the LCP film adhered to the copper foil) at a temperature at least 30°C lower than the melting point of the LCP, the thermal fusion between the LCP fibers or between the LCP fibers progresses, and the mechanical strength of the LCP film is further improved. Furthermore, by heat treating at a temperature at least 30°C lower than the melting point of the LCP, the crystal structure of the LCP in the LCP film changes, and the molecular chains of the LCP become more entangled with each other, thereby improving the mechanical strength of the LCP film. In addition, when the filler raw material is an organic filler, the mechanical strength of the LCP film may be improved by the heat treatment described above, which promotes thermal fusion between the fillers. In addition, if the heating temperature is not higher than a temperature 10°C higher than the melting point of the LCP, the flow of the LCP fibers and the filler raw material is suppressed, and the linear expansion coefficient in the main in-plane direction of the LCP film can be suppressed from increasing.

[0086] The heating time in the heat treatment step (S5) is not particularly limited and may be, for example, 1 second or more, or 10 seconds or more. In addition, since the variation in the crystal structure of the LCP in the LCP film is reduced by holding for a long period of time, the heating time may be, for example, 10 minutes or more, or 60 minutes or more.

[0087] The heating atmosphere in the heat treatment step (S5) is preferably an inert gas atmosphere such as nitrogen or argon, or a vacuum atmosphere. The oxygen concentration in the heating atmosphere is preferably 10,000 ppm or less, more preferably 1,000 ppm or less.

[0088] (Light irradiation process: S6) Fig. 9 is a flow diagram showing a second modified example of the manufacturing process of the liquid crystal polymer film of the embodiment. As shown in Fig. 9, the manufacturing method of the liquid crystal polymer film according to the present embodiment may further include a light irradiation process (S6) after the heat pressing process (S3). The light irradiation process (S6) may be performed before the heat treatment process (S6) and the metal foil removal process (S4) as shown in Fig. 9, or may be performed immediately after the heat treatment process (S5) or the metal foil removal process (S4).

[0089] A flash lamp, for example, can be used as the light irradiation device in the light irradiation step (S6). A specific example of the light irradiation device is PulseForge (registered trademark) 1300 manufactured by NovaCentrix. EXAMPLES

[0090] The present disclosure will be described in more detail below by way of examples, but the present disclosure is not limited to these examples.

[0091] <Example 1> (Production of liquid crystal polymer powder) In Example 1, first, uniaxially oriented LCP pellets (cylindrical pellets with a diameter of 3 to 4 mm, melting point: 315° C.) were prepared as the LCP raw material. The LCP material was a block copolymer of parahydroxybenzoic acid and 4,6-hydroxynaphthoic acid.

[0092] This LCP raw material was coarsely pulverized using a cutter mill (MF10 manufactured by IKA). The coarsely pulverized LCP was passed through a 3 mm diameter mesh provided at the outlet of the cutter mill to obtain coarsely pulverized LCP.

[0093] Next, the coarsely ground LCP was finely ground in a liquid nitrogen bead mill (Imex Corporation, LNM-08, vessel capacity: 0.8 L). Specifically, 500 mL of media and 30 g of the coarsely ground LCP were placed in a vessel and ground for 120 minutes at a rotation speed of 2000 rpm. The media used were zirconia (ZrO 2 ) beads were used. In the liquid nitrogen bead mill, the coarsely pulverized LCP is dispersed in liquid nitrogen and then wet-pulverized. In this way, the coarsely pulverized LCP was pulverized in the liquid nitrogen bead mill to obtain granular finely pulverized LCP.

[0094] The particle size of this finely ground LCP was measured. In the particle size measurement, the finely ground LCP dispersed in the dispersion medium was subjected to ultrasonic treatment for 10 seconds, and then set in a particle size distribution measuring device (LA-950, manufactured by Horiba, Ltd.) using a laser diffraction scattering method, and the particle size was measured. As the dispersion medium, Ekinen (registered trademark, Japan Alcohol Sales Co., Ltd.), a mixed solvent mainly composed of ethanol, was used. The measured value of D50 of the finely ground LCP was 23 μm.

[0095] Next, the dispersion liquid obtained by dispersing the finely pulverized LCP in the equene was sieved through a mesh with an opening of 100 μm to remove the coarse particles contained in the finely pulverized LCP, and the finely pulverized LCP that passed through the mesh was collected. The yield of the finely pulverized LCP after removing the coarse particles was 85% by mass.

[0096] Next, the finely pulverized LCP from which the coarse particles had been removed was dispersed in a 20% by mass ethanol solution. The ethanol slurry in which the finely pulverized LCP was dispersed was repeatedly crushed five times using a wet high-pressure crushing device under conditions of a nozzle diameter of 0.2 mm and a pressure of 200 MPa, to form fibers. As the wet high-pressure crushing device, a high-pressure disperser (Nanoveita manufactured by Yoshida Kikai Kogyo Co., Ltd.) was used. The ethanol slurry in which the finely pulverized LCP was dispersed was dried using a spray dryer to obtain an LCP powder. The average fiber diameter measured for 100 LCP fibers contained in the LCP powder was 0.8 μm.

[0097] (Production of liquid crystal polymer films) As a filler raw material, perfluoroalkoxy fluororesin (PFA resin) (irregular shape, average particle size: 2 μm, melting point: 300° C.) was prepared.

[0098] The PFA resin and the LCP powder obtained above were dispersed in butanediol, a dispersion medium, to form a paste. The mixing ratio of the PFA resin to the LCP powder was 3:7 by volume.

[0099] Next, the paste-like mixture was applied to the roughened surface of an electrolytic copper foil (FWJ-WS-12, manufactured by Furukawa Electric Co., Ltd.) measuring 180 mm square and 12 μm thick, using a metal plate measuring 160 mm square. The electrolytic copper foil to which the paste-like mixture was applied was heated to 180° C. on a hot plate to vaporize the butanediol dispersion medium, thereby drying the paste-like mixture on the electrolytic copper foil. In this way, a thin LCP fiber mat was formed on the electrolytic copper foil.

[0100] The above paste mixture was further applied onto this thin LCP fiber mat. The applied paste mixture was dried in the same manner as the previously applied paste mixture was dried. In this way, the above application and drying were repeated several times, and the basis weight was increased to 35 g / m2. 2 The LCP fiber mat was formed on an electrolytic copper foil.

[0101] Next, the LCP fiber mat formed on the electrolytic copper foil was hot-pressed together with the electrolytic copper foil using a high-temperature press. Specifically, a release film was first laminated on the side of the LCP fiber mat formed on the electrolytic copper foil opposite to the electrolytic copper foil. A polyimide film (Kapton (registered trademark) 100H, manufactured by Toray DuPont Co., Ltd.) was used as the release film. Then, the LCP fiber mat laminated with the release film was set in the high-temperature press. The set LCP fiber mat was pressed together with the release film and the electrolytic copper foil at a temperature of 295°C and a press pressure of 6 MPa for 10 seconds. The size of the pressing member used for pressing was 170 mm square. After the hot press, the release film was removed to obtain FCCL.

[0102] Finally, the electrolytic copper foil that was bonded to the LCP film was removed by etching with an aqueous solution of ferric chloride. This resulted in the production of an LCP film. The thickness of the LCP film was 25 μm.

[0103] <Example 2> In Example 2, the same PFA resin as in Example 1 was used as the filler raw material, but the PFA resin was repeatedly crushed 20 times using a wet high-pressure crushing device (Starburst Lab, manufactured by Sugino Machine Co., Ltd.) under conditions of a nozzle diameter of 0.18 mm and a pressure of 200 MPa to micronize the PFA resin. In addition, FCCL and LCP films were produced using the same production process as in Example 1, except that the same LCP powder as in Example 1 and the micronized PFA resin obtained above were pressed for 5 minutes using the same vacuum high-temperature pressing device as in Example 1 at a temperature of 310°C and a pressing pressure of 6 MPa.

[0104] <Example 3> In Example 3, an LCP fiber mat was formed by a papermaking method using PTFE micropowder (irregular shape, average particle size: 0.2 μm, melting point: 327° C.) as a filler raw material.

[0105] The PTFE micropowder and the same LCP powder as in Example 1 were dispersed in a 50% by mass ethanol aqueous solution as a dispersion medium to form a slurry. The mixing ratio of the PTFE micropowder and the LCP powder was 3:7 by volume.

[0106] Next, the slurry mixture was placed on an 80-mesh wire net and then coated with a polyester microfiber nonwoven fabric (basis weight: 14 g / m 2 ) using a square sheet machine (Kumagaya Riki Kogyo Co., Ltd.) to obtain an LCP fiber mat. The weight of the LCP fiber mat was set to 2.55 g so that the thickness of the LCP film was 25 μm. The LCP fiber mat was then dried in a hot air dryer and transferred onto the same electrolytic copper foil as in Example 1 to form an LCP fiber mat. FCCL and an LCP film were produced using the same production process as in Example 1, except that the LCP fiber mat was formed by a papermaking method.

[0107] <Example 4> In Example 4, uniaxially oriented LCP pellets (cylindrical pellets with a diameter of 3 to 4 mm, melting point: 340°C) were prepared as the LCP raw material. The LCP material was a block copolymer of parahydroxybenzoic acid and 4,6-hydroxynaphthoic acid. Except for changing the LCP raw material to the above, an LCP powder was produced in the same manner as in Example 1. The average fiber diameter measured for 100 LCP fibers contained in the LCP powder was 1.4 μm.

[0108] FCCL and LCP films were produced using the same production process as in Example 1, except that the same PTFE micropowder as in Example 3 and the LCP powder obtained above were pressed for 10 seconds at a temperature of 310°C and a pressing pressure of 6 MPa using a vacuum high-temperature press device similar to that in Example 1.

[0109] <Example 5> In Example 5, PPE powder (irregular shape, average particle size: 4.5 μm, melting point: 290° C.) was used as the filler raw material. This was obtained by coarsely pulverizing and finely pulverizing PPE pellets using the same cutter mill and liquid nitrogen bead mill used in the production of the LCP powder in Example 1 under the same conditions. FCCL and LCP films were produced using the same production process as in Example 1, except that the filler raw material was the PPE powder.

[0110] <Example 6> In Example 6, FCCL and LCP films were produced in the same manner as in Example 1, except that finely ground talc (plate-like, average particle size: 2.7 μm) was used as the filler raw material.

[0111] <Example 7> In Example 7, the ethanol slurry in which the finely pulverized LCP was dispersed was repeatedly crushed 30 times using a wet high-pressure crushing device (Starburst Lab, manufactured by Sugino Machine Co., Ltd.) under conditions of a nozzle diameter of 0.18 mm and a pressure of 200 MPa to produce LCP powder by the same manufacturing process as in Example 1, except that the fiber diameter measured for 100 LCP fibers contained in the LCP powder was 0.6 μm. As a filler raw material, the same PFA resin as in Example 1 was prepared. Then, FCCL and LCP films were produced by the same manufacturing method as in Example 3, except that these LCP powders and PFA resins were used, and the LCP fiber mat was pressed together with a release film and an electrolytic copper foil at a temperature of 310° C. and a press pressure of 6 MPa for 300 seconds.

[0112] <Example 8> In Example 8, the ethanol slurry in which the finely pulverized LCP was dispersed was crushed once using a wet high-pressure crushing device (Starburst Lab, manufactured by Sugino Machine Co., Ltd.) under conditions of a nozzle diameter of 0.18 mm and a pressure of 200 MPa to produce LCP powder by the same manufacturing process as in Example 1. The average fiber diameter measured for 100 LCP fibers contained in the LCP powder was 1.7 μm. FCCL and LCP films were produced by the same manufacturing method as in Example 7, except that this LCP powder was used.

[0113] <Example 9> In Example 9, the ethanol slurry in which the finely pulverized LCP was dispersed was repeatedly crushed 90 times using a wet high-pressure crushing device (Starburst Lab, manufactured by Sugino Machine Co., Ltd.) under conditions of a nozzle diameter of 0.18 mm and a pressure of 200 MPa to produce LCP powder by the same manufacturing process as in Example 1. The average fiber diameter measured for 100 LCP fibers contained in the LCP powder was 0.07 μm. FCCL and LCP films were produced by the same manufacturing method as in Example 7, except that this LCP powder was used.

[0114] <Example 10> In Example 10, FCCL and LCP films were produced by the same production method as in Example 7, except that the mixing ratio of the PFA resin and the LCP powder was set to 4:6 by volume.

[0115] <Example 11> In Example 11, an FCCL and an LCP film were produced by the same production method as in Example 7, except that the mixing ratio of the PFA resin and the LCP powder was set to 5:5 by volume.

[0116] <Example 12> In Example 12, the LCP powder produced by the same manufacturing process as in Example 1 was subjected to wet ultraviolet treatment using a low-pressure mercury UV lamp under the conditions of a wavelength of 253.7 nm and a treatment time of 2 hours. The LCP powder before and after the treatment were each subjected to X-ray photoelectron spectroscopy (XPS) measurement. The measurement was performed using an ULVAC-PHI "Quantes I" XPS measurement device under the conditions of a measurement range of 1000 μm × 200 μm, an accumulation number of 2 times, and an energy range of 0 eV to 1200 eV. As a result of this measurement, it was confirmed that the oxygen atom content of the surface of the LCP powder after the treatment was increased compared to the LCP powder before the treatment. The same PFA resin as in Example 1 was prepared as the filler raw material. Then, FCCL and LCP films were produced by the same manufacturing method as in Example 3, except that this UV-treated LCP powder and the same PFA resin as in Example 1 were used, and the LCP fiber mat was pressed together with a release film and an electrolytic copper foil at a temperature of 310°C and a pressure of 6 MPa for 300 seconds.

[0117] <Example 13> In Example 13, an ethanol slurry was obtained by mixing the same PFA resin as in Example 1 with a 50 wt% ethanol aqueous solution. The ethanol slurry was subjected to 30 times of in-liquid nitrogen plasma discharge treatment under the conditions of an electrode material of SUS, a voltage of ±4 kV, and a nitrogen bubbling amount of 3 L / min. Thus, a plasma-treated PFA resin was obtained. XPS measurements were performed on the PFA resin before and after the treatment. The measurements were performed under the same measurement conditions as those used for measuring the LCP powder in Example 12. As a result of the measurements, it was confirmed that the carboxyl group content on the surface of the PFA resin after the treatment was increased compared to the PFA resin before the treatment. FCCL and LCP films were produced by the same production method as in Example 3, except that the plasma-treated PFA resin and LCP powder produced by the same production process as in Example 1 were used, and the LCP fiber mat was pressed together with a release film and an electrolytic copper foil at a temperature of 310° C. and a press pressure of 6 MPa for 300 seconds.

[0118] <Example 14> In Example 14, the PFA resin finely divided in the same manner as in Example 2 was mixed with a 50% by mass aqueous ethanol solution to obtain an ethanol slurry. The ethanol slurry was subjected to 30 times of in-liquid nitrogen plasma treatment under the conditions of an electrode material of SUS, a voltage of ±4 kV, and a nitrogen bubbling amount of 3 L / min. Thus, a plasma-treated PFA resin was obtained. The PFA resin before treatment and the PFA resin after treatment were each subjected to XPS measurement under the same conditions as in Example 13. As a result of this measurement, it was confirmed that the carboxyl group content on the surface of the PFA resin after treatment was increased compared to the PFA resin before treatment. FCCL and LCP films were produced by the same production method as in Example 3, except that the PFA resin thus treated and the LCP powder obtained by the same production process as in Example 1 were used, and that the LCP fiber mat was pressed together with a release film and an electrolytic copper foil at a temperature of 310° C. and a press pressure of 6 MPa for 300 seconds.

[0119] <Example 15> In Example 15, FCCL and LCP films were produced by the same production method as in Example 3, except that LCP powder that had been wet-UV treated in the same manner as in Example 12 and PFA resin that had been treated in the same manner as in Example 14 were used, and the LCP fiber mat was pressed together with a release film and an electrolytic copper foil at a temperature of 310° C. and a pressure of 6 MPa for 300 seconds.

[0120] <Example 16> In Example 16, the LCP fiber mat formed on the electrolytic copper foil was hot-pressed in the same manner as in Example 3, and then placed in an inert gas oven in which the temperature of the furnace atmosphere was controlled to 310° C. and the oxygen concentration was controlled to 20 ppm, and the heat treatment was performed by holding the oven for 1 hour to obtain an FCCL including a heat-treated LCP film. Then, an LCP film was obtained in the same manner as in Example 3.

[0121] <Example 17> In Example 17, the LCP fiber mat formed on the electrolytic copper foil was hot-pressed in the same manner as in Example 3, and then light irradiation and heat treatment were carried out in this order to obtain an FCCL. Specifically, in the light irradiation step, light irradiation treatment was carried out using a light irradiation device (NovaCentrix PulseForge (registered trademark) 1300). The irradiation voltage was 270 V, the pulse length was 3.5 m, the irradiation surface was the LCP film side, and the number of irradiations was 30. In the heat treatment step, the FCCL containing the LCP irradiated with light as described above was placed in an inert gas oven in which the temperature of the furnace atmosphere was controlled to 310° C. and the oxygen concentration was controlled to 20 ppm, and the FCCL was heat-treated by holding it for 1 hour to obtain an FCCL containing a heat-treated LCP film. Then, an LCP film was obtained by the same method as in Example 3.

[0122] <Comparative Example 1> In Comparative Example 1, FCCL and LCP films were produced in the same manner as in Example 1, except that alumina silica (spherical, average particle size: 4 μm) which is an inorganic hollow filler was used as the filler raw material.

[0123] <Comparative Example 2> In Comparative Example 2, an FCCL and an LCP film were produced using the same LCP powder and filler raw materials as in Example 1, and using the same high-temperature press device as in Example 1, with the temperature set to 310°C and the press pressure set to 2 MPa for 10 seconds, except that the LCP powder and filler raw materials were used and pressed using the same high-temperature press device as in Example 1, with the temperature set to 310°C and the press pressure set to 2 MPa for

[0124] <Reference example 1> In Reference Example 1, FCCL and LCP films were produced in the same manufacturing process as in Example 3, except that uniaxially oriented LCP pellets (cylindrical pellets with a diameter of 3 to 4 mm, melting point: 320°C) were used as the LCP raw material, and that in the dispersion process, only the LCP powder was dispersed in butanediol, which is a dispersion medium, to form a paste, and the mixture of the LCP powder and the dispersion medium in the paste form was applied to the roughened surface of the electrolytic copper foil. Therefore, the LCP film according to Reference Example 1 does not contain a filler. The measured value of D50 of the finely pulverized LCP, the yield of the finely pulverized LCP by removing the coarse particles, and the average fiber diameter measured for 100 LCP fibers contained in the LCP powder were the same as those in Example 3 (Example 1).

[0125] <Reference example 2> In Reference Example 2, the LCP fiber mat formed on the electrolytic copper foil was hot-pressed in the same manner as in Reference Example 1, and then placed in an inert gas oven in which the temperature of the furnace atmosphere was controlled to 310° C. and the oxygen concentration was controlled to 20 ppm, and the heat treatment was performed by holding the oven for 1 hour to obtain an FCCL including a heat-treated LCP film. Then, an LCP film was obtained in the same manner as in Reference Example 1.

[0126] [Observation of liquid crystal polymer film] Figures 1 to 4 are photographs (SEM images) of the cross sections of the LCP films in Example 1, Example 2, Comparative Example 1, and Comparative Example 2. From the photographs in Figures 1 to 4, it can be seen that the LCP films of the examples contain flat fillers and filler aggregates that are thinner and longer (larger aspect ratio) than the LCP films of the comparative examples, and that the major axis of the flat fillers is oriented in the LCP film so as to be approximately parallel to the thickness direction. It can also be seen that the LCP films of the comparative examples contain a large amount of fillers that are not flat but are closer to spherical.

[0127] [Measurement of average aspect ratio and average slope of filler] For the LCP films according to Examples 1 to 15 and Comparative Examples 1 and 2, the average aspect ratio of the filler and the inclination of the filler with respect to the thickness direction of the LCP film were measured by the above-mentioned measurement method. These results are shown in the "Average aspect ratio" and "Inclination (°)" columns of Table 1. The averages were calculated for 90 fillers in Example 1, 80 fillers in Examples 2 to 6, 90 fillers in Examples 7 to 13, 80 fillers in Example 14, 90 fillers in Example 15, 80 fillers in Comparative Example 1, and 55 fillers in Comparative Example 2. Fillers with an area smaller than that of a perfect circle with a diameter of 1 / 100 or less of the thickness of the LCP film were excluded from the measurement, and fillers with an aspect ratio of the major axis to the minor axis within 1.1 were considered to be perfect spheres, with an aspect ratio of 1 and an inclination of 45°.

[0128] [Measurement of linear expansion coefficient] The CTE in the main plane was measured for each of the LCP films according to Examples 1 to 15 and Comparative Examples 1 and 2. Specifically, the CTE in the main plane (XY direction) of the LCP film was measured by a TMA (thermo-mechanical analysis) method in accordance with JIS K 7197. The TMA conditions were as follows: using a thermal analyzer (TMA4030SA, manufactured by Bruker), the temperature was raised from room temperature to 150°C in a nitrogen atmosphere, and then cooled to room temperature at 10°C / min, the load was 10g, the sample shape was a strip (5mm x 10mm), and the CTE was measured between 80°C and 40°C during the cooling process. The measurement results of the CTE of the LCP film are shown in the "CTE (ppm / °C)" column of Table 1.

[0129] [Measurement of warpage] The amount of warpage was measured for each of the FCCLs according to Examples 1 to 15 and Comparative Examples 1 and 2. Specifically, a 150 mm square FCCL was placed on a glass plate with the copper foil side facing down, and the distances from the corners of the FCCL to the glass plate were measured, and the average value was taken as the amount of warpage. The measurement results of the amount of warpage of the FCCL are shown in the "Amount of warpage (mm)" column of Table 1. Note that when the FCCL warps too much, it becomes cylindrical, and the distances from the corners to the glass plate cannot be measured. When the FCCL becomes cylindrical with a circumference of 150 mm, the distance of the corners from the glass plate is at a maximum value (about 48 mm), so that the cylindrical shape was determined as "48 mm or more."

[0130] [MIT folding endurance measurement] The LCP films according to Examples 1 to 3 and 12 to 15 were subjected to an MIT folding endurance test. Specifically, a part of the LCP film was cut out to obtain a rectangular test piece having a width of 1 cm and a length of 10 cm. The number of times this test piece could be folded back and forth until it broke (MIT folding endurance) was measured using an MIT folding endurance tester under the conditions of a load of 500 g, a bending clamp curvature radius of 0.2 mm, a bending angle of 135 degrees, and a folding speed of 175 cpm. The measurement results of the MIT folding endurance are shown in Table 2.

[0131] [Measurement of breaking strength and breaking elongation] The LCP films according to Examples 3, 16 and 17 and Reference Examples 1 and 2 were subjected to a tensile test to measure the breaking strength and breaking elongation. Specifically, a part of the LCP film was first cut out to obtain a strip-shaped test piece having a width of 5 mm and a length of 30 mm. The test piece was pulled using a tensile tester (TA Instruments' "RSA-G2") under a nitrogen atmosphere under conditions of a gap width of 13 mm, a speed of 0.01 mm / s and a temperature of 25°C, and the load was measured until the specimen broke, thereby measuring the breaking strength and breaking elongation. The measurement results of the breaking strength and breaking elongation are shown in Tables 3 and 4.

[0132] [Measurement of the first melting point (Tm1) and the second melting point (Tm2)] The first melting point (Tm1) and the second melting point (Tm2) of the LCP in the LCP film were measured by performing differential scanning calorimetry (DSC) on the LCP films according to Examples 3, 16, and 17 and Reference Examples 1 and 2. First, the LCP film was heated from room temperature to 370°C at a rate of 20°C / min to completely melt it, and the temperature at the endothermic peak that appeared at that time was taken as the first melting point (Tm1) of the LCP in the LCP film. If multiple endothermic peaks were observed at this time, the highest temperature among the temperatures at the multiple endothermic peaks was taken as the first melting point (Tm1) of the LCP in the LCP film. Thereafter, the melt of the LCP film was cooled to 175°C at a rate of 20°C / min, and the temperature at the endothermic peak that appeared when the melt was again heated to 370°C at a rate of 20°C / min was taken as the second melting point (Tm2) of the LCP in the LCP film. In this case, when multiple endothermic peaks were observed, the highest temperature among the temperatures of the multiple endothermic peaks was determined as the second melting point (Tm2) of the LCP in the LCP film. The measurement results of the first melting point (Tm1) and the second melting point (Tm2) of each of the above LCP films, and the temperature difference (ΔTm = Tm2 - Tm1) calculated by subtracting the first melting point (Tm1) from the second melting point (Tm2) are shown in Tables 3 and 4.

[0133] [Wide-angle X-ray scattering measurement] Wide-angle X-ray scattering measurements (WAXS) were performed on the LCP films according to each of Reference Examples 1 and 2. The wide-angle X-ray scattering measurements were performed by attaching the LCP film to a measurement cell and using a transmission method. In the scattering intensity profile obtained in the above measurement, the scattering intensity values ​​at a diffraction angle of 21.2 degrees at which scattering from the (200) plane of the orthorhombic crystal system was observed are shown in Table 4. The scattering intensity values ​​shown in Table 4 are values ​​normalized by the peak with the highest scattering intensity in the scattering intensity profile (i.e., values ​​when the maximum scattering intensity in the above scattering intensity profile is set to 1).

[0134] [Table 1]

[0135] [Table 2]

[0136] [Table 3]

[0137] [Table 4]

[0138] As shown in Table 1, the LCP films according to Examples 1 to 15, in which the average aspect ratio of the filler is 3 or more and the inclination of the filler relative to the thickness direction of the LCP film is within 15°, have a lower CTE than those of Comparative Examples 1 and 2. It is also found that the amount of warping of the FCCL is reduced in proportion to the CTE value. This can also be confirmed from the photographs of the FCCL of Example 1 in FIG. 5 and Comparative Example 1 in FIG. 6. Note that Example 6 uses an inorganic filler as the filler raw material, and has the lowest CTE and amount of warping compared to the other Examples, but is inferior in flexibility compared to the other Examples. It can be said that the LCP films of Examples 1 to 5, which use a flexible organic filler, are suitable for FPC boards (flexible circuit boards).

[0139] Furthermore, as shown in Table 1, in Examples 7 and 9, which were produced using LCP with an average diameter of 0.07 μm to 1.4 μm, the CTE and FCCL warpage in the plane of the LCP film are reduced compared to Example 8, which has an average diameter of 1.7 μm. If the average diameter of the fiber diameter of the fibrous LCP powder is 0.07 μm to 1.4 μm, the average diameter of the fiber diameter of the LCP powder is relatively small, so that the fibrous LCP powder particles are less likely to ride over each other. This makes it easier for the LCP to be oriented in the plane during the production of the LCP film, and it is believed that the CTE and FCCL warpage in the plane of the LCP film are reduced.

[0140] Furthermore, as shown in Tables 1 and 2, the LCP film according to Example 12 obtained using the LCP powder whose surface is treated with ultraviolet light has an increased MIT folding endurance and improved strength compared to the LCP films according to Examples 1 and 3. The LCP film according to Example 13 obtained using the filler whose surface is treated with plasma has an increased MIT folding endurance and improved strength compared to Examples 1 and 3. The LCP film according to Example 14 obtained using the filler whose surface is treated with plasma has an increased MIT folding endurance and improved strength compared to Example 2. The LCP film according to Example 15 obtained using the LCP powder whose surface is treated with ultraviolet light and the filler whose surface is treated with plasma has an increased MIT folding endurance and improved strength compared to Examples 12 to 14. In this way, it is believed that by treating the surface of the LCP powder or the filler in advance, the interfacial adhesion between the LCP powder and the filler is improved, and the film strength is improved. Furthermore, it is believed that by treating the surfaces of both the LCP powder and the filler in advance, the affinity between these materials is improved, and the film strength is further improved.

[0141] In addition, as shown in Table 3, the LCP films according to Examples 16 and 17, which are heat-treated at a temperature 30°C lower than the melting point of the liquid crystal polymer and 10°C higher than the melting point of the liquid crystal polymer after the hot press process and have a temperature difference (Tm) of 10°C or more, have improved breaking elongation compared to the LCP film according to Example 3, which is not heat-treated during production and has a temperature difference (Tm) of less than 10°C. The LCP film according to Example 16 also has improved breaking strength compared to the LCP film according to Example 3. It is believed that the mechanical strength of the LCP film is further improved by the heat treatment as described above, which sufficiently fuses the LCP fibers in the LCP film, changes the crystal structure of the LCP in the LCP film, and further entangles the molecular chains of the LCP with each other.

[0142] Furthermore, as shown in Table 3, the temperature difference (ΔTm) is larger and the breaking elongation is further improved in Example 17 compared to the LCP films of Examples 3 and 16, which were not subjected to the above-mentioned light irradiation. Therefore, it is considered that the above-mentioned light irradiation causes the LCP fibers to be more fused to each other on the surface of the LCP film, changing the crystal structure of the LCP, thereby further improving the breaking elongation of the LCP film.

[0143] As shown in Table 4, the LCP film according to Reference Example 1, which is not heat-treated during production and has a temperature difference (Tm) of less than 10° C., is heat-treated after the hot press process at a temperature 30° C. lower than the melting point of the liquid crystal polymer and 10° C. higher than the melting point of the liquid crystal polymer, and has a temperature difference (Tm) of 10° C. or more. The LCP film according to Reference Example 2 has improved breaking strength and breaking elongation. Compared with the LCP film according to Reference Example 1, the LCP film according to Reference Example 2 has a low scattering intensity derived from the (200) plane of the orthorhombic crystal system in the WAXS scattering profile. Therefore, the LCP film according to Reference Example 2 has a reduced number of LCP crystal layers in the LCP film compared to the LCP film according to Reference Example 1. Thus, it can be understood from Reference Examples 1 and 2 that the heat treatment under the above conditions actually changes the crystal structure of the LCP in the LCP film, and the molecular chains of the LCP are further entangled with each other, thereby improving the breaking strength and breaking elongation of the LCP film, and thus improving the mechanical strength.

[0144] In the above description of the embodiments, configurations that can be combined may be combined with each other.

[0145] The embodiments and examples disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims.

Claims

1. A liquid crystal polymer film comprising a liquid crystal polymer and a filler, The filler includes a flat filler, The average aspect ratio of the filler is 3 or more; A liquid crystal polymer film, wherein an average inclination of the filler with respect to a main surface direction of the liquid crystal polymer film is within 15°.

2. 2. The liquid crystal polymer film according to claim 1, wherein a ratio of a content of the filler to a total content of the liquid crystal polymer and the filler is 30 vol % or more and 50 vol % or less.

3. 3. The liquid crystal polymer film according to claim 1, which has an MIT folding endurance of 130 or more.

4. The liquid crystal polymer film according to claim 1 or 2, wherein the filler is an organic filler.

5. The liquid crystal polymer film according to claim 4 , wherein the filler is a perfluoroalkoxy fluororesin.

6. A method for producing the liquid crystal polymer film according to claim 1, A dispersing step of dispersing the liquid crystal polymer powder and the filler in a dispersion medium to obtain a paste or slurry-like mixture; a matting step of drying the paste or slurry mixture to form a mixture mat; and a hot pressing step of hot pressing the mixture mat to obtain a liquid crystal polymer film.

7. The method for producing a liquid crystal polymer film according to claim 6 , wherein the liquid crystal polymer powder contains fibrous particles made of a liquid crystal polymer.

8. The method for producing a liquid crystal polymer film according to claim 7, wherein the average diameter of the fibrous particles made of the liquid crystal polymer is 0.07 μm or more and 1.4 μm or less.

9. The method for producing a liquid crystal polymer film according to claim 6 , wherein the filler has an average particle size of 1 μm or less.

10. The average particle size of the filler is greater than 1 μm, The method for producing a liquid crystal polymer film according to claim 6 , wherein the heating temperature in the hot pressing step is within a range of ±10° C. of the melting point of the filler.

11. The method for producing a liquid crystal polymer film according to claim 6 , wherein in the hot pressing step, the mixture mat is hot pressed together with a copper foil.

12. The method for producing a liquid crystal polymer film according to claim 6 , wherein the mattifying step includes a coating step of coating the paste-like mixture on a copper foil.

13. The method for producing a liquid crystal polymer film according to claim 6 , wherein in the mat-forming step, the mixture in a slurry state is formed into the mixture mat by a papermaking method.

14. The method for producing a liquid crystal polymer film according to claim 6 , wherein the liquid crystal polymer powder has a surface that has been treated with ultraviolet light.

15. The method for producing a liquid crystal polymer film according to claim 6 , wherein the filler has a surface that is plasma-treated.

16. The liquid crystal polymer powder has a surface that has been treated with ultraviolet light, The method for producing a liquid crystal polymer film according to claim 6 , wherein the filler has a surface that is plasma-treated.

17. The method for producing a liquid crystal polymer film according to any one of claims 6 to 8, further comprising a step of heat-treating the liquid crystal polymer film at a temperature that is at least 30°C lower than the melting point of the liquid crystal polymer powder and at most 10°C higher than the melting point of the liquid crystal polymer powder after the heat pressing step.

18. The method for producing a liquid crystal polymer film according to claim 6 , further comprising a step of irradiating the liquid crystal polymer film with light after the heat pressing step.

Citation Information

Patent Citations

  • Liquid-crystal polyester solution composition

    JP2004315678A

  • Method for producing liquid crystal polymer film and liquid crystal polymer film

    JP2014111699A

  • Laminated plate and metal base circuit board

    JP2018029187A

  • Resin composition for printed circuit boards and production method

    JP2019065061A

  • Liquid composition, liquid crystal polyester film and method for producing liquid crystal polyester film, and laminate film and method for producing laminate film

    JP2021095520A